Human neural stem cells in patients with chronic ischaemic stroke (PISCES): a phase 1, first-in-man study. Issue 10046 (20th August 2016) - Kalladka, Dheeraj; Sinden, John; Pollock, Kenneth; Haig, Caroline; McLean, John; Smith, Wilma; McConnachie, Alex; Santosh, Celestine; Bath, Philip M; Dunn, Laurence; Muir, Keith W
Summary: Background: CTX0E03 is an immortalised human neural stem-cell line from which a drug product (CTX-DP) was developed for allogeneic therapy. Dose-dependent improvement in sensorimotor function in rats implanted with CTX-DP 4 weeks after middle cerebral artery occlusion stroke prompted investigation of the safety and tolerability of this treatment in stroke patients. Methods: We did an open-label, single-site, dose-escalation study. Men aged 60 years or older with stable disability (National Institutes of Health Stroke Scale [NIHSS] score ≥6 and modified Rankin Scale score 2–4) 6–60 months after ischaemic stroke were implanted with single doses of 2 million, 5 million, 10 million, or 20 million cells by stereotactic ipsilateral putamen injection. Clinical and brain imaging data were collected over 2 years. The primary endpoint was safety (adverse events and neurological change). This trial is registered withClinicalTrials.gov, numberNCT01151124 . Findings: 13 men were recruited between September, 2010, and January, 2013, of whom 11 (mean age 69 years, range 60–82) received CTX-DP. Median NIHSS score before implantation was 7 (IQR 6–8) and the mean time from stroke was 29 (SD 14) months. Three men had subcortical infarcts only and seven had right-hemisphere infarcts. No immunological or cell-related adverse events were seen. Other adverse events were related to the procedure or comorbidities. Hyperintensity around the injection tracts on T2-weighted fluid-attenuation inversion recovery MRI was seen in five patients. At 2 years, improvement in NIHSS score ranged from 0 to 5 (median 2) points. Interpretation: Single intracerebral doses of CTX-DP up to 20 million cells induced no adverse events and were associated with improved neurological function. Our observations support further investigation of CTX-DP in stroke patients. Funding: ReNeuron Limited.